2000
DOI: 10.1046/j.1365-277x.2000.00228.x
|View full text |Cite
|
Sign up to set email alerts
|

The development and testing of a food portion photograph book for use in an African population

Abstract: OBJECTIVE: To develop and test a book of photographs of commonly eaten foods to be used as a visual aid in the description of portion sizes in a large cross-sectional study on the health profile of Africans in transition (THUSA - Transition, Health and Urbanization in South Africa). SETTING: Clinics in the North West Province of South Africa. PARTICIPANTS: One hundred and sixty-nine adult African volunteers DESIGN: Data on commonly eaten foods, preparation methods, recipes and portion sizes were collected in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
1
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(151 citation statements)
references
References 19 publications
6
140
1
4
Order By: Relevance
“…more favourable nutrient intake (positive impact), these effects were only measured in the short term and usually in the laboratory setting (88)(89)(90)(91)(92)(93)(94)(95)(96)(97) . A follow-up study conducted 3 months after initial training about SS showed that the immediate positive impact had not been maintained (96) .…”
Section: Consumer Understandingmentioning
confidence: 99%
“…more favourable nutrient intake (positive impact), these effects were only measured in the short term and usually in the laboratory setting (88)(89)(90)(91)(92)(93)(94)(95)(96)(97) . A follow-up study conducted 3 months after initial training about SS showed that the immediate positive impact had not been maintained (96) .…”
Section: Consumer Understandingmentioning
confidence: 99%
“…Standard household measuring utensils, rulers and validated food photographs of typical South African foods (Venter et al, 2000) were used to quantify food portion sizes. The recorded quantities of food consumed were converted to gram weights using the Medical Research Council Food Quantities Manual (Langenhoven et al, 1991a).…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…Kirkcaldy-Hargreaves et al (18) used life-sized colour pictures and found that their validity was similar to or slightly higher than that for life-sized food drawings, soft plastic food models and models with abstract shapes. In South Africa, Venter et al (15) tested near life-size (A4) photographs and found relatively good results: 68 % of the estimates were within 610 % of the actual portion size. However, due to the differences in the experimental Table 4 Proportion of participants classified in the same or opposite thirds of the distribution of estimated and actual food consumption and proportion of participants whose estimates were design, it is difficult to compare the results with the present study.…”
Section: Discussionmentioning
confidence: 99%